Risk management of public-private partnership charging infrastructure projects in China based on a three-dimension framework. (15th December 2018) - Wu, Yunna; Song, Zixin; Li, Lingwenying; Xu, Ruhang
Abstract: As electric vehicles present booming development in China, insufficient supply of charging infrastructure has become a serious issue which hinders the development of electric vehicles. Under this circumstance, public-private-partnership mode is introduced to attract private capital so as to promote the construction of charging infrastructure. Nevertheless, the public-private-partnership charging infrastructure project, with characteristics of high investment, many participants and long payback period, possesses high risks including political risks, economic risks, technical risks and participants risks for all the project participants. To better implement the project, this paper proposes a risk management framework to control risks. First, a comprehensive risk index system is established using Delphi method. Second, a three-dimension model including probability, losses and uncontrollability are employed for risk assessment in which analytic hierarchy process method is used for weight determination and grey fuzzy method is employed for assessment. Finally, risks are allocated to different participants and corresponding countermeasures are put forward. This paper presents a comprehensive study of risk assessment, risk sharing scheme and risk response measures for the public-private partnership charging infrastructure. And furthermore, the result is helpful for both the concessioner and the grantor to develop equitable concession agreements, take measures to manage risks and further achieve win-win goal. Highlights: A comprehensive risk index system concerning the PPP charging infrastructure is established. A three-dimension framework consisting of possibility, uncontrollability and losses is employed for risk management. ANP-grey fuzzy comprehensive assessment method is utilized for risk assessment. Risks are allocated to different participants and risk countermeasures are proposed.